1998
DOI: 10.1215/10642684-4-2-159
|View full text |Cite
|
Sign up to set email alerts
|

Sex Change and the Popular Press: Historical Notes on Transsexuality in the United States, 1930–1955

Abstract: , the New York Daily News announced the "sex change" surgery of Christine Jorgensen. The front-page headline read "Ex-GI Becomes Blonde Beauty: Operations Transform Bronx Youth," and the story told how Jorgensen had traveled to Denmark for "a rare and complicated treatment." The initial scoop soon escalated into an international media frenzy. Reporters cast Jorgensen, who was young and beautiful, as a starlet on the rise, and within two weeks had sent out fifty thousand words on her through the news wire servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 6 publications
0
24
0
1
Order By: Relevance
“…The extant literature on news media representations of transgenderism in particular consists mostly of case studies of news coverage of public figures (Capuzza, 2015;Meyerowitz, 1998;Pieper, 2013;Skidmore, 2011) and hate-crime victims (Barker-Plummer, 2013;Chvez, 2010;MacKenzie & Marcel, 2009;Sloop, 2000;Squires & Brouwer, 2002;Willox, 2003). As noted by Spencer (2015) and Capuzza (2015), this literature demonstrates the ways in which news media coverage disciplines and stereotypes transgender identity (see also Barker-Plummer, 2013;Cloud, 2014;Sloop, 2004).…”
Section: Transgenderism In the Newsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extant literature on news media representations of transgenderism in particular consists mostly of case studies of news coverage of public figures (Capuzza, 2015;Meyerowitz, 1998;Pieper, 2013;Skidmore, 2011) and hate-crime victims (Barker-Plummer, 2013;Chvez, 2010;MacKenzie & Marcel, 2009;Sloop, 2000;Squires & Brouwer, 2002;Willox, 2003). As noted by Spencer (2015) and Capuzza (2015), this literature demonstrates the ways in which news media coverage disciplines and stereotypes transgender identity (see also Barker-Plummer, 2013;Cloud, 2014;Sloop, 2004).…”
Section: Transgenderism In the Newsmentioning
confidence: 99%
“…Finally, news media coverage of transgender issues and individuals frequently sexualizes the transgender body, primarily through focus on sexual organs as the source of gender identity (Cram, 2012;Landau, 2012;Meyerowitz, 1998;Ryan, 2009;Schilt & Westbrook, 2009;Sloop, 2000;Squires & Brouwer, 2002), as well as through the portrayal of transgender women in particular as hypersexual (MacKenzie & Marcel, 2009). This sexualization continues a trend that began with coverage of Christine Jorgensen in the 1950s, which focused on her sexual organs as proof of her "legitimate" transition to womanhood (Meyerowitz, 1998). News coverage of Brandon Teena, for example, focused obsessively on his anatomy-primarily that he did not have a penis-and placed a particular focus on his sexual relationships with women (Sloop, 2000), sifting through the details of his anatomy and sexual history to determine how to locate his gender.…”
Section: Transgenderism In the Newsmentioning
confidence: 99%
“…Mainstream news media have a history of marginalising, stereotyping and pathologizing representations of trans people (Barker-Plummer 2013). Ever since the public "transformation" of American trans woman Christine Jorgensen in the 1950s was among the first to cause headlines, trans people have often been covered in a sensationalistic way by news media (Arune 2006;Cloud 2014;Hackl, Becker, and Todd 2016;Meyerowitz 1998). Often figuring in soft news stories (Capuzza 2014(Capuzza , 2016, research has found tabloids to cover trans issues in a particularly delegitimising manner (Billard 2016).…”
Section: Representations Of Trans People In the Mediamentioning
confidence: 99%
“…For the original article that Benjamin responded to in his letter, see Worden and Marsh (1955). For secondary analyses of Benjamin's work, the case of Jorgensen's sexchange surgery, and a general history of transsexuality in the United States, see Meyerowitz (1998Meyerowitz ( , 2002. For the argument that advancements in medical technology provided the precondition for the emergence of modern transsexualism and the concept of gender, see Hausman (1995).…”
Section: Affecting Medicinementioning
confidence: 99%